Failing securely: The processes and support which underpin English nurse mentors' assessment decisions regarding under-performing students. (April 2016) - Hunt, Louise A.; McGee, Paula; Gutteridge, Robin; Hughes, Malcolm
Summary: Background: This study was undertaken in response to concerns that mentors who assessed practical competence were reluctant to fail student nurses which generated doubts about the fitness to practise of some registered nurses. Limited evidence was available about the experiences of mentors who had failed underperforming students and what had helped them to do this. Aim: To investigate what enabled some mentors to fail underperforming students when it was recognised that many were hesitant to do so. Method: An ethically approved, grounded theory approach was used to explore thirty-one nurses' experiences of failing student nurses in practical assessments in England. Participants were recruited using theoretical sampling techniques. Semi-structured interviews were conducted. Analysis was undertaken using iterative, constant comparative techniques and reflexive processes. The theoretical framework which emerged had strong resonance with professionals. Findings: Five categories emerged from the findings: (1) Braving the assessment vortex; (2) Identifying the 'gist' of underperformance; (3) Tempering Reproach; (4) Standing up to scrutiny; and (5) Drawing on an interpersonal network. These categories together revealed that mentors needed to feel secure to fail a student nurse in a practical assessment and that they used a three stage decision making process to ascertain if this was the case. Many of the components which helped mentors to feel secure were informal in nature and functioned on goodwill and local arrangements rather than on timely, formal, organisational systems. The mentor's partner/spouse and practice education facilitator or link lecturer were identified as the key people who provided essential emotional support during this challenging experience. Conclusion: This study contributes to understanding of the combined supportive elements required for robust practical assessment. It presents a new explanatory framework about how mentors formulate the decision to fail a student nurse and the supportive structures which are necessary for this to occur. Highlights: Mentors needed social support to feel secure enough to fail underperforming students. Mentors undertook a three stage process to decide if they would fail an underperforming student nurse. Practice Education Facilitators and husbands, wives and partners provided the main support. The systems and processes which enabled mentors to fail students were often based on goodwill and informal support. Key actions involved providing emotional, appraisal, instrumental and informational support.